The Conversational Implicature Found while Trevor Noah Criticizes the Government in Stand-up Comedy Show - Hartono, Missherly Angelia Steffani (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2023)
This research deals with conversational implicature and flouted maxim found in stand-up comedy. This descriptive qualitative research, analyzed 12 utterances of Trevor Noah from YouTube video entitled â€œTrevor Noah COMPLETE REMARKS at 2022 White House Correspondentsâ€™ Dinner (C-SPAN)â€ using Griceâ€™s conversational implicature theory. The finding shows that from 12 utterances, every utterance can contain more than one type of flouted maxims, the details are as follows, 10 manner, 9 quality, 7 relevance, 6 maxims of quantity. The researcher also finds that, Noah applied Particularized Conversational Implicature more frequently than Generalized Conversational Implicature, with a ratio of 11:1. Noah has done this to make his satire is less offensive. This research also finds that flouted of maxims does not mean that a conversation has been failed, but that is intentionally done by the speaker to create an implicature effect in his utterance. As long as the speaker and the listener have the same knowledge about the context or background, the conversation will keep going well.